The oral microbiome and atherosclerosis: current evidence on association, mechanisms, and clinical implications - Xiao, Yan; Gong, Bin; Li, Jing; Xu, Nan (Frontiers in Immunology, 2025)
Atherosclerosis, the primary pathology of cardiovascular disease (CVD), is not fully explained by traditional risk factors. The oral microbiome has emerged as a key environmental contributor, yet the evidence for its role remains complex. This review moves beyond summarizing established associations to critically appraise the evidence, synthesize novel mechanistic insights, and outline future clinical frameworks. While traditional mechanisms such as direct bacteremia and systemic inflammation are covered, this review highlights emerging pathways including the oral-gut-vascular axis, epigenetic reprogramming ("inflammatory memory"), and the role of the multi-kingdom microbiome. We critically evaluate the evidence landscape, reconciling conflicting findings from observational studies, Mendelian randomization, and randomized controlled trials (RCTs) by systematically examining methodological heterogeneity. Furthermore, future directions are explored, focusing on the application of artificial intelligence (AI) for biomarker discovery and the development of novel interventions like engineered microbial therapeutics. Finally, the review translates scientific consensus into actionable clinical frameworks for interdisciplinary patient care. This comprehensive synthesis underscores the need to move towards mechanism-based, personalized strategies for CVD prevention.